Fighting the Crisis, Readjusting the Economic Model Die Krise bekämpfen, das Wirtschaftsmodell neu justieren - Grimm, Veronika; von Rüden, Christina (Wirtschaftsdienst, 2022)
Tackling the crisis, readjusting the economic model: Rising energy prices, historically high inflation rates and ongoing supply chain bottlenecks are challenging Germany’s long-standing industrial base. On top of that, entrepreneurs and the state alike are faced with new geopolitical tensions forcing them to re-evaluate existing (trade) relationships. In order to strengthen Germany’s attractiveness as an industrial location in the long term and to emerge from this crisis more resilient to economic and geopolitical changes, its economic model needs to be readjusted. In this article, we thus discuss key areas of action, including how to secure energy supply, how to diversify international relationships, as well as how to provide sustainable and targeted support to firms that does not prevent structural change.
CRIS-Team Scopus Importer:2023-03-07